How to debrief teamwork interactions: using circular questions to explore and change team interaction patterns. Issue 1 (January 2016) - Kolbe, Michaela; Marty, Adrian; Seelandt, Julia; Grande, Bastian
Abstract We submit that interaction patterns within healthcare teams should be more comprehensively explored during debriefings in simulation-based training because of their importance for clinical performance. We describe howcircular questions can be used for that purpose. Circular questions are based on social constructivism. They include a variety of systemic interviewing methods. The goals of circular questions are to explore the mutual dependency of team members' behavior and recurrent behavior patterns, to generate information, to foster perspective taking, to "fluidize" problems, and to put actions into relational contexts. We describe the nature of circular questions, the benefits they offer, and ways of applying them during debriefings.